Biogenic Calcium Oxide Nanoparticles: Green Synthesis, Hemocompatibility and Dye Adsorption Studies - Malarvizhi, A.; Packiam, C. Stella; Joyce, M.I. Delighta Mano; Gomathi, R.; Christy, H. Kohila Subathra (Asian Journal of Chemistry, 2026)
Calcium oxide (CaO) is a highly efficient chemisorbent and catalyst for the mitigation of hazardous gases, rendering it an important material in industrial and environmental applications. In present study, CaO nanoparticles (CaO NPs) were synthesised using a green hydrothermal approach using the marine squid (Sepioteuthis lessoniana) ethanol extract as a natural precursor. XRD analysis confirmed the crystalline nature, with an average crystallite size of 48.12 nm as estimated using the Debye-Scherrer equation. The successful conversion of the marine squid extract into CaO NPs was verified by FTIR and XRD analyses. Transmission electron microscopy (TEM) revealed spherical nanoparticles with an average particle size of approximately 50 nm. Field emission scanning electron microscopy (FESEM) images showed predominantly spherical particles with porous, rough surfaces and aggregation observed at the elevated temperatures. The synthesised CaO NPs demonstrated a high adsorption efficiency toward methyl red (MR) dye, with a maximum adsorption capacity of 42.34 mg/g and a Freundlich constant (Kf) of 22.45 (mg/g)(mg/L)ⁿ. Adsorption data exhibited an excellent fit with the Langmuir and Freundlich isotherm models, while Temkin isotherm and quantum chemical analyses suggested that the adsorption mechanism was predominantly physical in nature.